Peningkatan Kemampuan Membaca Melalui Media Bahan Bekas di TK Al-Qur’an Ijtihad Sikalang Sawahlunto - Nurul Khairunnisa; Serli Marlina (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This study aims to improve early childhood reading skills through the use of recycled materials. The low interest and reading ability of group B children at the Al-Quran Ijtihad Sikalang Kindergarten in Sawahlunto City is the background of this study, where learning is still dominated by conventional methods that lack variety. This type of research is Classroom Action Research (CAR) which was carried out in two cycles, with each cycle consisting of three meetings. The subjects were 15 children in group B. Data collection techniques used observation, documentation, and performance assessment. The results showed a significant increase in each cycle. In the pre-cycle condition, classical mastery only reached 4%. After the Cycle I action, children's abilities began to develop but were not optimal. Rapid improvement occurred in Cycle II with the use of environmental print media (real product packaging), where classical mastery reached 95% with the categories Developing According to Expectations (BSH) and Developing Very Well (BSB). It was concluded that recycled materials media are effective in creating contextual, enjoyable learning and significantly improving children's early reading skills.